2022
DOI: 10.3171/2021.10.focus21505
|View full text |Cite
|
Sign up to set email alerts
|

Robotic and robot-assisted skull base neurosurgery: systematic review of current applications and future directions

Abstract: OBJECTIVE The utility of robotic instrumentation is expanding in neurosurgery. Despite this, successful examples of robotic implementation for endoscopic endonasal or skull base neurosurgery remain limited. Therefore, the authors performed a systematic review of the literature to identify all articles that used robotic systems to access the sella or anterior, middle, or posterior cranial fossae. METHODS A systematic review of MEDLINE and PubMed in accordance with PRISMA guidelines performed for articles publ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…In a literature review, Pangal et al [ 27 ] reviewed 22 articles on robotic skull base neurosurgery, as well as flexible endoscopy using The Flex system [ 28 ], Versius [ 29 ]. Carrau et al [ 1 ] and Chauvet et al [ 30 ] have reported clinically on transoral skull base surgery.…”
Section: Discussionmentioning
confidence: 99%
“…In a literature review, Pangal et al [ 27 ] reviewed 22 articles on robotic skull base neurosurgery, as well as flexible endoscopy using The Flex system [ 28 ], Versius [ 29 ]. Carrau et al [ 1 ] and Chauvet et al [ 30 ] have reported clinically on transoral skull base surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, challenges arise from the manipulation of the robotic arms, simultaneous insertion of a camera, and safety issues associated with operating these devices. Therefore, previous studies concluded that it is difficult to implement in clinical practice due to these limitations [22].…”
Section: Discussionmentioning
confidence: 99%
“…Despite significant advances made in robotic-assisted surgery, the translation of such systems into endonasal skull-base surgery has been slow. 14 While studies have demonstrated the feasibility of robotic endoscope holders, 14 the only robot capable of tissue manipulation that has undergone clinical trials for skull-base surgery is the DaVinci system (Intuitive, Surgical). 15,16 However, the Da Vinci was built for general surgery and thus faces challenges related to its instruments' size, operating room footprint, and lack of dedicated tools (e.g., drills) when deployed for pituitary surgery.…”
Section: Comparison With the Literaturementioning
confidence: 99%
“…15,16 Indeed, the DaVinci cannot be inserted through the nose and thus must currently rely on transoral approaches to the sella. 14 Examples of robots purpose-built for endoscopic skull base surgery can be found in the preclinical stage of translation, in which continuum robots are popular. Such teleoperated "flexible robots" consist of thin, flexible, tubular shafts with interchangeable end-effectors capable of tissue manipulation.…”
Section: Comparison With the Literaturementioning
confidence: 99%